Merancang Key Performance Indicator (KPI) Warehouse di PT SIM – Bekasi - . Basuki (Politeknik Kelapa Sawit Citra Widya Edukasi, 2019)
PT SIM is a leading automotive company in Indonesia which produces two-wheeled vehicles and four-wheeled vehicles. This company requires a lot of raw materials or components to make these products. The components are imported from local and imported suppliers. Especially for imported components, storage is carried out in a warehouse before it is used or produced. PT SIM has used a Warehouse Management System (WMS) to facilitate the control of the inventory, because the amount is very much. Even though we have used an integrated system, but there are no indicators to measure the success of warehouse operations, so it is necessary to do research on indicators of warehouse performance success. The purpose of this study is to design a way to measure the performance of the Warehouse against targets that have been determined using the Key Performance Indicator (KPI). The KPIs element used refers to the activity at the warehouse, ie Receiving, Put away, Storage, Unpacking, Picking and Fulfilment, so it will be determined formulation that can describe a value that can be measured its success. The result of this study indicate that there is a performance report format that can be used to measure the success of warehouse operations at PT SIM.